Favourable exploration lithofacies of hybrid sedimentary shales in the Dongpu depression, Bohai Bay Basin - Duan, Jinbao; Xu, Yunlong; Yuan, Bo; Li, Lingxi; Xu, Tianwu; Wang, Debo; Chao, Kai; Yang, Dongdong; Li, Honglei (Frontiers in Earth Science, 2025)
Hybrid sedimentary shales (HSS) are key components of continental shale oil resources. The inherent heterogeneity of HSS lead to rapid variations in oil content and mobility, complicating sweet spot prediction. Previous studies have classified HSS lithofacies and assessed oil content. However, favourable lithofacies for oil content and mobility remains debated. This study classified the Shahejie Formation HSS from the Dongpu Depression, Bohai Bay Basin into massive argillaceous shale (Lithofacies I), bedded argillaceous shale (Lithofacies II), and laminated calcareous shale (Lithofacies III) based on sedimentary texture, mineral composition, and total organic carbon (TOC) content. The light hydrocarbon calibrated oil content (S1C), oil mobility (OSI), and micro-migration hydrocarbon content (δQ) variations among these lithofacies were conducted to determine favourable oil content and mobility lithofacies. Results show that the Lithofacies III exhibited the highest average TOC (1.56 w. t. %), hydrogen index (HI) (264 mg/g TOC), oil content (S1C = 1.81 mg/g), and oil mobility (OSI = 188 mg/g TOC). Geochemical data revealed that Lithofacies III also display the most pronounced micro-migration (average δQ = −138 mg/g TOC). TOC, Tmax, and δQ influence the oil content of HSS, with TOC being the primary factor, suggesting that shales with high organic matter abundance possess better hydrocarbon generation potential and can produce more shale oil. Conversely, δQ, clay minerals, and carbonate minerals affect oil mobility, with δQ being the dominant factor, highlighting the role of micro-migration in pore connectivity, transport, and enrichment of shale oil within the extramicro-migration and intramicro-migration units. Global comparisons show that micro-migration drives HSS oil enrichment, while sedimentary environment and tectonic setting influence oil content and mobility. This study provides new insights into key factors controlling HSS oil micro-migration and enrichment, advancing global exploration and development of HSS resources.